2021
DOI: 10.2147/hmer.s292251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MicroRNA-122 as a Biomarker for Chronic Hepatitis C Infection and as a Predictor for Treatment Response to Direct-Acting Antivirals

Abstract: Background: Treatment response to antiviral drugs is a challenging issue in patients with chronic hepatitis C virus (HCV) infection. Although microRNA-122 represents the majority of the microRNA content in hepatic tissues, few studies have evaluated its role in the treatment response, so we aimed to study its role in chronic HCV patients and in predicting the treatment response to direct-acting antivirals (DAAs). Methods: The study included 125 chronic HCV patients (89 naïve and 36 with a prior failed peginter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…In this work we noticed that obtaining SVR12 was linked to considerable increase in PLT count, which begins at the end of treatment and lasts for up to 12 months. Come online with our findings Elabd et al has reported significant elevation of platelet count after achieving HCV eradication by DAAs 16 . Additionally, Sayyar et al has concluded that PLT improvement following HCV eradication is most likely due to viral eradication and should not be used or construed as a measure of liver fibrosis or portal hypertension improvement only 17 .…”
Section: Discussionsupporting
confidence: 78%
“…In this work we noticed that obtaining SVR12 was linked to considerable increase in PLT count, which begins at the end of treatment and lasts for up to 12 months. Come online with our findings Elabd et al has reported significant elevation of platelet count after achieving HCV eradication by DAAs 16 . Additionally, Sayyar et al has concluded that PLT improvement following HCV eradication is most likely due to viral eradication and should not be used or construed as a measure of liver fibrosis or portal hypertension improvement only 17 .…”
Section: Discussionsupporting
confidence: 78%
“…The 5 UTR IRES is responsible for initiation of HCV viral RNA translation by facilitating its binding to the ribosomal subunit. The microRNA-122 is a liver-specific human microRNA which has an important role in HCV viral replication inside the liver cell [42,43]. Interestingly, binding of microRNA-122 to viral RNA results in upregulation of both HCV RNA and genes that are related to plasma cholesterol and hepatic fatty-acid metabolism [44,45].…”
Section: Hcv Replication Assembly and Releasementioning
confidence: 99%
“…With the release of the HCV genome into the cytosol, HCV interacts with different lipid-associated factors to promote viral replication, assembly and release. As a liver-specific miRNA, miRNA-122 plays an important role in HCV replication [62]. The binding of miRNA-122 to viral RNA leads to the upregulation of genes involved in lipid metabolism [63].…”
Section: Hepatitis C Virusmentioning
confidence: 99%